The 1691 G → A Mutation in the Factor V Gene: Relationship to Activated Protein C (APC) Resistance and Thrombosis in 65 Patients - Leroy-Matheron, Catherine; Levent, Martine; Pignon, Jean-Michel; Mendonça, Caio; Gouault-Heilmann, Michèle (Thrombosis and Haemostasis, 1996)
Four hundred fifty subjects were screened for the 1691 G → A mutation in the factor V gene. Two hundred ninety-seven patients were referred to us for unexplained thrombosis, 133 were family members of these patients and 20 were normal subjects. We studied the relationships between the mutation, resistance to APC and thrombosis. Among the 450 subjects tested, 65 belonging to 42 families were found to have the 1691 G → A mutation in one (n = 61) or both alleles (n = 4). The prevalence of the mutation in the thrombotic patients was 13%. Resistance to APC was tested for in 247 subjects not on anticoagulant treatment (4 homozygous and 44 heterozygous for the mutation, and 199 individuals without the mutation). Incomplete cosegregation of heterozygosity for the 1691 G → A mutation with APC resistance (APC-SR <2.4 or n-APC-SR <0.75) was observed, showing that the functional assay alone is insufficient for a firm diagnosis. In patients carrying the mutation, elevated levels of prothrombin fragment 1+2 and D-dimers pointed to increased thrombin generation in vivo. Clinical manifestations in the heterozygous subjects were very similar to those reported in heterozygous PC or PS deficiencies, but the first thrombotic event occurred later than in PC- or PS-deficient patients. Homozygosity for the factor V gene mutation appears to be a far more benign thrombotic disorder than homozygous PC and PS deficiencies.